2018
DOI: 10.1037/dhe0000046
|View full text |Cite
|
Sign up to set email alerts
|

Other duties not assigned: Experiences of lesbian and gay student affairs professionals at small colleges and universities.

Abstract: This study examined how lesbian and gay student affairs professionals negotiate their sexual identity within the institutional culture and professional responsibilities at small colleges and universities (SCUs). Nineteen individuals participated in semistructured interviews. Using the concept of theoretical bricolage (Kincheloe, 2005;Kincheloe, McLaren, & Steinberg, 2011), this study paired interpretivism and critical theory to explore how power mediated disclosure of sexual identity, enactment of identity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…These findings are similar to those of Kortegast and van der Toorn’s (2018) qualitative study about LGBTQ student affairs professionals at small colleges. The authors reported that while their participants’ job responsibilities required supporting students, they described engaging in service beyond their job description because of their own identity as LGBTQ persons.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are similar to those of Kortegast and van der Toorn’s (2018) qualitative study about LGBTQ student affairs professionals at small colleges. The authors reported that while their participants’ job responsibilities required supporting students, they described engaging in service beyond their job description because of their own identity as LGBTQ persons.…”
Section: Discussionsupporting
confidence: 86%
“…LGBTQRCs first appeared in student affairs in 1971 (Fine, 2012) initially to serve sexual minoritized (later trans* and gender minoritized) students, to combat hostile campus environments and lack of institutional policies and practices (Evans & Rankin, 1998;Marine, 2011). Kortegast and van der Toorn (2018) pointed out there is a gap in the literature about LGBTQ+ professionals in general, which echoes claims made by other scholars about LGBTQRC staff (Marine, 2011;Pryor, Garvey, & Johnson, 2017;Sanlo, 2000).…”
Section: Literature Reviewmentioning
confidence: 69%
“…However, as D‐L Stewart observed, “racially and ethnically minoritized students are always already gritty because, too often, they have had to deal with toxic educational environments” (Stewart, , p. 631). Prior research demonstrates that this is also the case for student affairs professionals who are racially and ethnically minoritized (Linder, Harris, Allen, & Hubain, ) and who identify as lesbian and gay (Kortegast & van der Toorn, ). Our stories in this chapter confirm and augment these findings in relation to our salient minoritized identities.…”
Section: Learning From the Complexities: Implications For Practicementioning
confidence: 99%